The Role of Technology in High-tech Agricultural Development in the Context of Social, Ecological and Economic Transformation in Vietnam - Ngoc Anh, Nguyen Thi (VNU Journal of Science: Policy and Management Studies; Vol 36 No 1, 2020)
The world has come to the point that requires more agricultural production using less resource. Moreover, the previous important elements for agricultural growth such as water, land, and human resources no longer play the decisive roles in the agricultural development. Instead, the application of high technology is the “key solution” for countries that depend on the agricultural economy like Vietnam. In Vietnam, agriculture is a particular economic sector that uses the majority of natural and human resources of the country. In the context of the social, ecological and economic transformation, the development of high-tech agriculture is not only about economic efficiency but also the issues of sustainable environmental development. High technology will be the solution to this multi-objective problem. The paper focuses on assessing the necessity of high-tech agricultural development and analyzing the role of technology in high-tech agricultural development, especially in the context that contains many challenges and opportunities.